1993
DOI: 10.1017/s0950268800056752
|View full text |Cite
|
Sign up to set email alerts
|

The haemagglutinins of influenza A (H1N1) viruses in the ‘O’ or ‘D’ phases exhibit biological and antigenic differences

Abstract: SummaryInfluenza A (H1N1) viruses when initially isolated in mammalian cell cultures (MDCK cells) had different agglutination reactions with chicken and guinea-pig erythrocytes compared to the same viruses after passage. On first isolation the virus HA resembled the ‘O’ phase viruses described originally by Burnet and Bull and agglutinated mammalian but not avian erythrocytes. After passage, the virus HA resembled a classical ‘D’ phase virus and agglutinated both avian and mammalian erythrocytes. Monoclonal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Group I viruses agglutinated goose, human and guineapig erythrocytes and CRBC, while group 2 viruses agglutinated the first three but not CRBC. Azzi et al (1993) also reported the same phenomenon in recently isolated HIN1 viruses. The candidate viral protein for host-specific haemagglutination was considered to be the HA glycoprotein.…”
Section: Introductionsupporting
confidence: 64%
“…Group I viruses agglutinated goose, human and guineapig erythrocytes and CRBC, while group 2 viruses agglutinated the first three but not CRBC. Azzi et al (1993) also reported the same phenomenon in recently isolated HIN1 viruses. The candidate viral protein for host-specific haemagglutination was considered to be the HA glycoprotein.…”
Section: Introductionsupporting
confidence: 64%
“…Minor antigenic variants within a heterogeneous population cannot be assessed by the serological method of HI (Patterson and Oxford, 1986). More importantly, mutations of the receptor binding site in HA (Nobusawa and Nakajima, 1988) (antigenic drift) are causing human seasonal H1N1 (Azzi et al, 1993; Morishita et al, 1993) and H3N2 influenza A viruses (Nobusawa et al, 2000) to lose the ability to bind to RBCs. For example, the mutations at residues 193, 196, 197, and 225 in the human epidemic H1N1 influenza A viruses in 1988 or later caused the loss of their abilities to agglutinate chicken RBCs due to four amino acid changes (Morishita et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The other approach is to perform the reassortment process with PR8 virus in the primary chicken embryo kidney cells instead of eggs. Both ways are associated with the emergence of the adaptation mutations in the HA protein that can change the receptor-binding and antigenic properties, or change the pH of HA fusion [25][26][27].…”
Section: Virus Adaptation Passages and Their Consequencesmentioning
confidence: 99%